Analisis Bibliometrik Penelitian dengan Tema "Digital Archive" - Wibowo, Edi; Salim, Tamara Adriani (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2022)
This study aims to analyze the development of the topic of digital archives in order to find solutions to various problems in managing digital archives with the risks caused by the creation of digital archives. The method used is literature review related to digital archives published between 1982 and 2022 taken from Scopus database. “Digital archives” is used as a keyword to reach relevant publications. VOSviewer was applied to perform a bibliometric analysis of this article. A total of 1218 publications on the topic of digital archives with a total link strength of 1821 appeared as the most frequent keywords, having strong links to "digital library" and "metadata". In 1988 - 2015 digital archives articles experienced a significant increase. Current growth trends predict a large increase in the number of global publications on digital archives. The top two countries that contribute the most of digital archive research topics are the United States (354 articles) and the United Kingdom (142 articles). Born digital, personal digital archives, metadata standards and digital assets may become hot topics of research in the future.